2013
DOI: 10.1007/s00345-013-1057-8
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based survey of lower urinary tract symptoms (LUTS) and symptom-specific bother: results from the Brazilian LUTS epidemiology study (BLUES)

Abstract: This is the largest population-based survey of LUTS in Brazil, using the 2002 ICS definitions. LUTS prevalence was high and increased with age among both genders in Brazil, whereas the rates of OAB were somewhat lower than previously reported. The high prevalence of urinary symptoms and the bother commonly associated with them highlight their importance to overall well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
8
30
2
6
Order By: Relevance
“…Individual prevalence comparisons may be more appropriate than overall prevalence comparisons among studies. LUTS in our study more commonly involved urinary storage problems rather than voiding difficulties, which were also reported for Western studies [6,7,14,17,18,20]. In the EPIC study, the ICS definition of nocturia (two or more voids per night) yielded similar prevalence (24.0%) to ours [7].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Individual prevalence comparisons may be more appropriate than overall prevalence comparisons among studies. LUTS in our study more commonly involved urinary storage problems rather than voiding difficulties, which were also reported for Western studies [6,7,14,17,18,20]. In the EPIC study, the ICS definition of nocturia (two or more voids per night) yielded similar prevalence (24.0%) to ours [7].…”
Section: Discussionsupporting
confidence: 84%
“…This information could assist in targeting patients who need intervention. Our study revealed similar findings to those of Moreira et al [6], who also noted that urgency was usually associated with moderate or severe bother, whereas nocturia was usually associated with minor bother. Our study is partly in line with those of Coyne et al [27] and Møller et al [28], who reported that the symptoms most frequently rated bothersome were nocturia, SUI, and urgency [27,28], and is similar to a national Finnish study that showed a high burden of urgency and UUI [29].…”
Section: Symptom-specific Bother Of Individual Lutssupporting
confidence: 93%
See 3 more Smart Citations